2016
DOI: 10.1136/annrheumdis-2016-eular.6042
|View full text |Cite
|
Sign up to set email alerts
|

OP0182 Prevention of Rheumatoid Arthritis by B Cell Directed Therapy in The Earliest Phase of The Disease: The Prairi Study

Abstract: BackgroundSystemic autoimmunity may precede the development of clinical signs and symptoms of seropositive rheumatoid arthritis (RA), which offers a window of opportunity to delay or prevent clinically manifest arthritis by targeted intervention. This could represent a paradigm shift from treatment to prevention1.ObjectivesTo explore if a single infusion of rituximab (anti-CD20 antibody) can prevent or delay the onset of clinically manifest arthritis in individuals at risk of developing autoantibody positive R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…Double seropositivity for ACPAs and RF was associated with the highest rates of inflammatory arthritis development and the shortest latency period, consistent with findings in other cohorts. Some practitioners treat ACPA/RF double‐seropositive individuals with hydroxychloroquine, and several ongoing clinical trials are targeting this patient population using other strategies . Surprisingly, the multistate modeling indicated that the likelihood of ACPA/RF double seropositivity reverting to seronegativity after 5 years was >30%.…”
Section: Discussionmentioning
confidence: 99%
“…Double seropositivity for ACPAs and RF was associated with the highest rates of inflammatory arthritis development and the shortest latency period, consistent with findings in other cohorts. Some practitioners treat ACPA/RF double‐seropositive individuals with hydroxychloroquine, and several ongoing clinical trials are targeting this patient population using other strategies . Surprisingly, the multistate modeling indicated that the likelihood of ACPA/RF double seropositivity reverting to seronegativity after 5 years was >30%.…”
Section: Discussionmentioning
confidence: 99%
“…Research efforts are therefore being directed toward the earliest stages of RA and toward the identification of biomarkers predictive of future RA development, to facilitate early treatment and preventive interventions for those at risk . Clinical trials are underway to evaluate therapeutic intervention for individuals with arthralgia but without clinically manifest arthritis , and promising early results may herald a paradigm shift from treatment toward prevention of RA .…”
Section: Introductionmentioning
confidence: 99%
“…Новые перспективы кардинального улучшения исхо-дов РА связаны с возможностью профилактики развития заболевания в «преартритической» фазе, проявляющейся так называемыми «клинически подозрительной артралги-ей» (clinically suspect arthralgia) или АЦЦП-позитивной артралгией, при которых годовой риск развития РА соста-вляет 32-35%, а трехлетний риск достигает 50% [138,139]. Предварительные результаты исследования PRAIRI (Prevention of RA by RItuximab) свидетельствуют о замедле-нии прогрессирования заболевания у пациентов с РФ/АЦБ-позитивными артралгиями и субклиническими признаками синовита, получивших инфузию анти-В-кле-точного препарата ритуксимаба [133]. В настоящее время запланирована серия исследований, касающихся оценки эффективности ГХ (исследование SropRA -Strategy to prevent the onset of clinically Apparent Rheumatoid Arthritis), МТ (TREAT EARLIER -Treat Early Arthralgia to Reverse or Limit Impending Exacerbation to Rheumatoid Arthritis), блокатора костимуляции Т-лимфоцитов АБЦ (APIPPRA -Arthritis Prevention In the Preclinical Phase of Rheumatoid Arthritis with Abatacept и ARIAA -Abatacept Reversing Subclinical Inflammation as Measured by MRI in ACCP Positive Arthralgia), аторвастатина (STAPRA -STAtins to Prevent Rheumatoid Arthritis) в отношении предотвращения РА у пациентов с артралгиями, имеющими риск развития РА.…”
Section: Discussionunclassified